Social characteristics of a child formed in the family during early childhood - Ochilova Farida Bakhriddinovna; Davlatova Durdona O'tkir kizi (Zien Journals, 2024)
This article discusses the formation of a child's social characteristics in early childhood and the impact of the child's social development in the family on the formation of relationships between representatives of the older generation and family members
Keywords: early childhood; representatives of the older generation; social characteristics